(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
It is well known that catalysts are used in the processes of developing new materials, catalysts are used that allow for the targeted transformation of raw materials. Catalysts based on rare, transitional and noble metals are widely used in industry. For more efficient use of metals, they are applied to various carriers that have a developed specific surface area, mechanical strength, resistance to aggressive environments, stability and inertia. Based on the above literature data, it is shown that catalysts obtained by physical methods have a higher conversion and catalytic activity compared to catalysts obtained by classical methods, such as impregnation or reduction methods. This article is devoted to a review of the literature on methods for obtaining catalysts on carbon carriers. The analysis of literary sources is designed toselection of methods of targeted modification of coals in Kyrgyzstan in order to obtain highly efficient carriers and synthesis of deposited catalysts.